2018
DOI: 10.1177/1528083718811086
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Azadirachta indica seed/spent Camellia sinensis bio-filler based jute fabrics–epoxy composites: Experimental and numerical studies

Abstract: The present work examined the thermo-mechanical characteristics of bio-fillers, namely Azadirachta indica seed powder, spent Camellia sinensis powder, their combinations filled jute fabrics–epoxy composites analytically and experimentally and compared it with the unfilled one. The test results showed that Azadirachta indica seed powder filled composites showed better mechanical properties with lesser voids, while spent Camellia sinensis powder and its composites showed better thermal stability. ANSYS analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(34 citation statements)
references
References 47 publications
2
32
0
Order By: Relevance
“…For proper distribution in the developed composites, a 25-kg per square feet of the load was applied in order to attain good distribution of matrix and better packing. It was kept untouched for 24 h in an ordinary environmental situation [15,16]. Care was taken to ensure that there were no air traps.…”
Section: (D)mentioning
confidence: 99%
See 1 more Smart Citation
“…For proper distribution in the developed composites, a 25-kg per square feet of the load was applied in order to attain good distribution of matrix and better packing. It was kept untouched for 24 h in an ordinary environmental situation [15,16]. Care was taken to ensure that there were no air traps.…”
Section: (D)mentioning
confidence: 99%
“…From the results, it was shown that the addition of SiC by 10 wt% improved tensile and flexural properties while the addition of SiC by 15 wt% showed better impact and hardness characteristics. Vijay et al [15] reinforced Azadirachta indica seed powder and spent Camellia sinensis powders as fillers in jute epoxy composites; the results revealed 10 wt% of azadirachta seed powder showed increase in mechanical properties and 10 wt% of spent Camellia sinensis fillers in composites showed better thermal stability due to the inorganic constituents present in it. Vinod et al [16] studied the thermomechanical behavior of calatropsis gigantea powder-filled jute-epoxy composites and found that 10 wt% of the fillers-based composites showed enhanced thermal stability and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…ρf, ρn and ρm are density of glass fiber, nanoclay and matrix respectively. ASTM D2734-94 standard is used to evaluate voids fraction of GFENC [19,20]. From the theoretical and actual densities of the GFENC, the void fraction is calculated by equation (2).…”
Section: Composite Specimen Preparationmentioning
confidence: 99%
“…It improved the compatibility between filler and polyester matrix [29]. Apart from that, natural fillers such as calotropis gigantean stem powder, azadirachta indica seed powder, spent camellia sinensis powder along with graphene powder was used for enhancing the properties of natural fiber composites [30][31][32]. In Southern part of India especially in Tamilnadu production of banana, sugar cane and coconut tree are plenty.…”
Section: Introductionmentioning
confidence: 99%